Analysis of the Influence of Macroeconomic Variables on Labor Absorption in Java Island - Agus Tri Basuki*; Defi Ratnawati (Universitas Syiah Kuala, 2023)
This study aims to analyze the effect of investment, inflation, minimum wage and gross regional domestic product (GRDP) on employment absorption in Java Island, Indonesia. The analytical tool used to analyze the research objectives is the panel data regression model. The selected regression result of this research is the Random Effect Model. The data used in this study uses data issued by the Indonesian Central Bureau of Statistics (DKI Jakarta in numbers, West Java in numbers, Central Java in numbers, West Java in numbers, East Java in numbers, DIY in numbers, and Banten in numbers) from 2013-2021 years. The results of the study show that domestic investment and GRDP have a positive influence on employment in Java. The Provincial Minimum Wage has a negative effect on employment, while foreign investment and inflation have no effect on employment in Java.